(untitled) (Circe de clásicos y modernos, 2018)
Given the intimacy in which slaves and their owners often lived, the servile threat was always latent and could be lethal. To keep the slaves under control and to get them to do their work, historians believe that a dual system of rewards and punishments –the carrot and the stick– was established in which the hope of manumission occupied a prominent place. In this article, we will try to show that manumission was not the main mechanism to obtain obedience from slaves, since there were other rewards at hand. As important as the double system of rewards and punishments were other mechanisms through which slaves assimilated their condition as natural and accepted it without protest.